2018
DOI: 10.1111/cas.13867
|View full text |Cite
|
Sign up to set email alerts
|

DEP domain containing 1 predicts prognosis of hepatocellular carcinoma patients and regulates tumor proliferation and metastasis

Abstract: DEP domain containing 1 (DEPDC1) protein is a novel oncoantigen upregulated in multiple types of cancers which present oncogenic activity and high immunogenicity. However, the function and therapeutic potential of DEPDC1 in hepatocellular carcinoma (HCC) remain unclear. In the present study, we showed that DEPDC1 was frequently upregulated in HCC and associated with cancer diagnosis and poor prognosis for HCC patients. Moreover, DEPDC1 promotes HCC cell proliferation in vitro as well as carcinogenesis in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…DEPDC1 downregulation also significantly inhibited tumourigenesis in xenograft mouse models, which may be due to the inhibition of cell proliferation and colony formation. Consistent with these results, Qu et al (13) demonstrated that DEPDC1 knockdown inhibited HCC cell proliferation, colony formation, migration and invasion. In addition, DEPDC1 silencing via siRNA reduced the viability and invasion capability of prostate cancer cell lines (24), while DEPDC1 upregulation promoted prostate cancer cell proliferation and metastases (25).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…DEPDC1 downregulation also significantly inhibited tumourigenesis in xenograft mouse models, which may be due to the inhibition of cell proliferation and colony formation. Consistent with these results, Qu et al (13) demonstrated that DEPDC1 knockdown inhibited HCC cell proliferation, colony formation, migration and invasion. In addition, DEPDC1 silencing via siRNA reduced the viability and invasion capability of prostate cancer cell lines (24), while DEPDC1 upregulation promoted prostate cancer cell proliferation and metastases (25).…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, DEPDC1 was revealed to be involved in the miR-130a-induced apoptosis and inhibition of proliferation in HepG2 cells (12). Qu et al (13) revealed that DEPDC1 promoted HCC cell proliferation and neoplasm metastasis. The present study also determined that DEPDC1 was positively correlated with the K-RAS signaling pathway, certain cancer-associated pathways and the WNT/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these DEmRNAs, we found that high DEPDC1 and CEP55 expression was associated with poor prognosis in patients with WT based on our survival analysis results. Several studies showed that the DEP domain containing 1 (DEPDC1) protein was a novel oncoantigen that was aberrantly overexpressed in multiple types of cancers [28,29]. DEPDC1 was shown to be negatively regulated by miR-26b and promoted cell proliferation and tumor growth by upregulating FOXM1 expression in triple-negative breast cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…DEPDC1 was selected as it was claimed to play an oncogenic function in carcinomas 19,22,25 and affect biological activities, such as cell proliferation, 22 apoptosis, 21 and metastasis. 18 As exhibited in Figure 3A, we obtained the predicted transcriptional regulation of TAF7 on DEPDC1 from UCSC Genome Browser. The result of luciferase reporter assay validated the upregulation of TAF7 purely enhanced the luciferase activity of WT DEPDC1 promoter ( Figure 3B).…”
Section: Mir-374c-5p Modulated Depdc1 By Mediating Taf7mentioning
confidence: 99%